Synod o rodzinie zwiastunem zmian? - Jakubiak, Tomasz (Ius Matrimoniale, 2015)
Points 84-86 Relatio concern a vital question which is participation in the life of Church of the divorced who started a new non-valid relationship. Decisions of people responsible for points 84-86 were affected by different motives. That is why the author wants to focus on theses “problematic” points and see whether they can be interpreter as “relaxing discipline of the Church”. Interpretation of points 84-86 Relatio presented by the author is one of many possible and has a solely scientific and theoretical dimension. The author avoiding stating his own views compared points 84-86 Relatio with the current discipline and practice of Church.